ANALISIS DIKSI DAN GAYA BAHASA DALAM HIKAYAT SOELTAN ATJEH MARHOEM (SOELTAN ISKANDAR MUDA) TERJEMAHAN T. MOHAMMAD SABIL - Nurlaili Nurlaili; Muhammad Iqbal (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
This research is entitled "Analysis of Diction and Language Style in the Hikayat Soeltan Atjeh Marhoem (Soeltan Iskandar Muda) Translation of T. Mohammad Sabil". The formulation of the problem in this research is "How is Diction and Language Style in the saga of Soeltan Atjeh Marhoem (Soeltan Iskandar Muda) T. Mohammad Sabil translation?". The purpose of this study is to describe the diction and style of the language contained in the saga Soeltan Atjeh Marhoem (Soeltan Iskandar Muda) translated by T. Mohammad Sabil. This study uses a descriptive method with a content analysis approach or content analysis. The data source of this research is the saga book Soeltan Atjeh Marhoem (Soeltan Iskandar Muda) translated by T. Mohammad Sabil. The data analysis technique in this study uses analytical-descriptive techniques, namely describing a clear picture of the depiction of diction and language style in the saga of Soeltan Atjeh Marhoem. The steps of analyzing the data are: (1) describing the data, (2) classifying the data, (3) analyzing and interpreting the data, then (4) drawing conclusions. Based on the results of the research, it was found that in the saga of Atjeh Marhoem (Soeltan Iskandar Muda) T. Mohammad Sabil's translation there are several types of diction, namely: denotation, connotation, abstract, concrete, general words, special words, foreign words, and absorption words. In addition, the saga of Atjeh Marhoem (Soeltan Iskandar Muda) Translated by T. Mohammad Sabil there are four types of language styles, namely (1) comparative language style, (2) repetition style, (3) obedience style, and (4) contradictory language style.